MANAJEMEN SUPERVISI KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR - Indra Eka Permana; Ricky Yoseptry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher professional competence is a key determinant of learning quality, yet many elementary school principals have not managed supervision systematically and sustainably, particularly in schools with limited resources. This study aims to analyze school principal supervision management in improving teachers' professional competence at SDN Bojongpicung 1 and SDN Cipeuyeum 3, Cianjur Regency, covering planning, implementation, evaluation, follow-up, constraints, solutions, and impact. A qualitative approach with a comparative case study method was used. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed using the Miles, Huberman, and Saldana model through data condensation, data display, and conclusion drawing. The results show that both principals have implemented supervision management in accordance with Deming’s Plan-Do-Check-Act cycle: needs-based planning, implementation with a humanistic approach and varied techniques, competency standard-based assessment instruments, and personalized follow-up. The constraints found were multidimensional, including administrative workload, capacity limitations, and human challenges such as resistance and low teacher confidence, which were addressed through task delegation, collaboration with senior teachers, and consistent positive reinforcement. Planned and sustained supervision proved to improve teachers’ content mastery, creativity in developing teaching materials, variation in teaching methods, and professional attitude. This study concludes that the effectiveness of principal supervision is determined by the quality of the overall management cycle, not merely by the completeness of administrative documents.